Durable Flexible Supercapacitors Utilizing the Multifunctional Role of Ionic Liquids. Issue 1 (23rd August 2017) - Lorenzo, Marta; Srinivasan, Geetha
Abstract: A simple scalable approach to design flexible, ultrathin, and safe supercapacitors to power up the next‐generation of portable electronics and implantable biomedical devices is reported. The main challenge to construct flexible supercapacitors is the development of flexible electrodes that can retain characteristics of high power density, long cycle life, and high efficiency during and after bending. In this work, flexible electrodes based on conducting polymer–biopolymer–ionic liquid–graphite composites that are chemically blended and stable have been prepared. They are used as electrodes in the fabrication of three devices, that is, (i) electrochemical, (ii) electrical double‐layer, and (iii) hybrid supercapacitors. The multifunctional role of ionic liquids as solvent, electrolyte, and plasticizer is exploited to fabricate these innovative supercapacitors. These flexible supercapacitors show specific capacitances of around 5 mF g −1, an operational voltage of about 2.2 V, and an excellent cycle life of >15 000 cycles with nearly 100 % efficiency. The design nature of these electrodes, chemical stability, and feasibility to use biocompatible components will enable the construction of task‐specific supercapacitors with excellent device stability. Abstract : Under the skin : Chemically blended polypyrrole–cellulose composites integrated with an ionic liquid shows potential for the fabrication of task‐specific and environmentally safe supercapacitors that are durable and flexible. These supercapacitors can be used to power up next‐generation electronic equipment and medical implants.